Perancangan Alat Pembaca Isyarat Tangan Wasit Service Badminton Menggunakan Sensor Flex - Jatmiko Kuntoro Nugroho; Achmad Rizal; Dien Rahmawati (eProceedings of Engineering, 2021)
Abstract— The badminton service referee is an important role in a match leader, not only leading in a match but also being a helper, enforcer, separator, court, in this final project the author can produce the best 100% accuracy and the lowest is 73% testing that focuses on trying movements one by one. Furthermore, for testing all movements the highest accuracy result was 87.5% and the lowest result was 62.5%. This is influenced by the continuous tool usage factor, the flex sensor which has a tolerance value of ± 30% and the influence of the quality of the sensor used. So that the results of the displayed image do not match. Another factor is that the tool fails to display the interface signal between Arduino Uno and Ms Visual Studio, which cannot appear on the screen. Keywords—badminton referee, judge service, sensor flex, accelerometer, arduino. Abstrak— Wasit Servis badminton merupakan peran penting dalam sebuah pemimpin pertandingan,tidak hanya memimpin dalam sebuah pertandingan namun juga bisa menjadi penolong, penegak, pemisah, pengadil, Tugas akhir ini penulis dapat menghasilkan akurasi terbaik 100% dan yang paling terendah adalah 73% pengujian yang berfokus mencoba gerakan satu per satu. Selanjutnya untuk pengujian semua gerakan mendapakatn hasil akurasi tertinggi 87.5% dan hasil paling terendah 62.5%. Hal ini dipengaruhi oleh faktor penggnaan alat terus menerus, sensor flex yang memiliki nilai toleransi ±30% dan pengaruh kualitas sensor yang digunakan. Sehingga hasil gambar yang ditampilkan tidak sesuai. Faktor lain alat tersebut gagal menampilkan gambar isyarat antarmuka antara Arduino uno dilayar. Kata Kunci— wasit bandminton, hakim service, sensor flex, akselerometer, arduino